2003
DOI: 10.4049/jimmunol.170.5.2516
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25− T Cells That Express Latency-Associated Peptide on the Surface Suppress CD4+CD45RBhigh-Induced Colitis by a TGF-β-Dependent Mechanism

Abstract: Murine CD4+CD25+ regulatory cells have been reported to express latency-associated peptide (LAP) and TGF-β on the surface after activation, and exert regulatory function by the membrane-bound TGF-β in vitro. We have now found that a small population of CD4+ T cells, both CD25+ and CD25−, can be stained with a goat anti-LAP polyclonal Ab without being stimulated. Virtually all these LAP+ cells are also positive for thrombospondin, which has the ability to convert latent TGF-β to the active form. In the CD4+CD45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
184
0
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(199 citation statements)
references
References 38 publications
4
184
0
5
Order By: Relevance
“…75 Conversely, TGF-␤ can regulate immunosuppressive regulatory T cells, and TSP1 has been implicated in regulating TGF-␤ activation by regulatory T cells. 76 It remains to be determined whether systemic blockade of TSP1-dependent latent TGF-␤ activation alters immune cell profiles in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…75 Conversely, TGF-␤ can regulate immunosuppressive regulatory T cells, and TSP1 has been implicated in regulating TGF-␤ activation by regulatory T cells. 76 It remains to be determined whether systemic blockade of TSP1-dependent latent TGF-␤ activation alters immune cell profiles in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…CD103 (integrin § E ) + (CD25 + or CD25 -) § g T R cells that express CTLA-4 protect mice from colitis pointing to CD103 as a marker for a T R cells subset apparently specialized for cross-talk with epithelial cells [13]. Activated, membrane TGF-g -expressing (CD25 + or CD25 -) T R cells suppress the manifestation of transfer colitis [14]. IL-10-producing CD4 + T R1 suppress proliferation of CD4 + T cells in response to antigen and prevent colitis induced in immunodeficient mice by transfer of CD4 + CD45RB hi T cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that activated CD4 + CD25 + T cells express an inactive form of TGF-b1 complexed to its latency associated peptide (LAP), a complex hypothesized to account for the enhanced suppressive capacity of activated CD4 + CD25 + T cells in vitro and in vivo [28,29]. On the other hand, Oida et al reported that TGF-bdependent suppression was observed in the LAP + CD4 + CD25 -T cell subset [33]. In addition, some studies have suggested a correlation between Treg effector function and the expression of a latent, membrane-bound form of TGF-b1 on CD4 + CD25 + Treg cells isolated from inflamed lymphoid tissues draining target organs undergoing autoimmune attack [30].…”
mentioning
confidence: 99%